PENERAPAN METODE DEBAT INISIASI BERORIENTASI KARAKTER TERHADAP KETERAMPILAN BERBICARA DAN BERPIKIR KREATIF SISWA SD - Supriatna, Irfan; ., Rahman (ATTA`DIB, 2016)
Students have problems speaking skills and creative thinking. Speaking considered difficult in learning activities in the classroom. To overcome this problem researchers conduct application-oriented character initiation debate in grade five elementary schools. This study aimed to obtain concrete evidence and describe the process of learning by using debate in the classroom so that an increase in student learning outcomes and responses to learning activities. This research method is quasi-experimental. This research was conducted at SDN 7 Hegarsari and involves 66 students consisting of 33 students and 33 students experimental class control. Research data in the form of pretest and posttest scores were analyzed using t-test. Based on data analysis, conclusions obtained by the average value of n-gain scores in the experimental class (0.50) is higher than the value of the average scores on the class n-gain control (0.35). Statistically significant difference between the two scores, the probability value obtained is smaller than the level specified significant (0.023 < 0.05). Students give a positive response to the learning process and it can be concluded that the application of effective character-oriented initiation debate improves speaking skills and creative thinking of students.